Determinants for stock market performance for Malaysia and United Kingdom / Nur Aisyah Faizal - Faizal, Nur Aisyah (2022)
Stock market is crucial not only for investors who wish to grow their wealth over time, but also for a country's economy as it can operate as one of the leading indications for a country's current and future economic state. The purpose of this study is to analyze the determinants for stock market performance for Malaysia and the United Kingdom. This research presents a study of the stock market in Malaysia and United Kingdom over the period of 201 i -2021. The total number of years observed in this study is 10. The independent variables in this study include consumer price index, crude oil price, inflation rate, and interest rate, whereas the dependent variable is the stock market performance for Malaysia and United Kingdom.